Mekanisme Pemberian Bantuan Hukum Bagi Masyarakat Miskin Di Pengadilan Negeri Samarinda - Jaidun, S.H., M.H (Yuriska: Jurnal Ilmiah Hukum, 2015)
ABSTRACT The court is a space or a last fort for people to get justice but in this case a problem which seek the court is not easy and with little expense but rather the cost to be incurred for example using the services of professional lawyers prohibitively expensive while not all people can afford to pay. However, Indonesia as a legal state as mentioned in the Constitution of 1945 in Article 1 point (3) "Indonesia is a legal state" the state must guarantee equality of each citizen both before the law and protect all the rights to be treated before the law, and with the Legal aid society, especially in the city of Samarinda, in this case, it helps people, especially the underprivileged in right of defending their rights and being protected from discrimination apparatus or elements which are not responsible and the process of case investigation encountered can occur as supposed to be. Thus, the law agencies is indispensable for the people belonging to the poor economy.